Is the protection against ischemia induced by red wine linked to its antioxidant capacity? - Mosca, Susana María (2001)
Objective: To establish whether the total antioxidant capacity of nonalcoholic extracts of three Argentine red wines (RWE) is correlated with their protection against ischemia-reperfusion injury. Animals and methods: The antioxidant properties of three RWE were determined using different free radicalgenerating systems. To examine the effects of these RWE during a 20 min global ischemic period followed by 30 min of reperfusion, isolated rat hearts received 50 µg/mL of RWE 1 (cabernetsauvignon), RWE 2 (malbec) or RWE 3 (a commercial mixture of cabernet-sauvignon, malbec and merlot) 10 min before and after ischemia. Left ventricular developed pressure (LVDP), maximal velocity of rise of left ventricular pressure (+dP/dtmax) and left ventricular end-diastolic pressure (LVEDP) were used to assess contractility and diastolic function. Results: All RWE inhibited lipid peroxidation induced by the Cl4C/NADPH system in a similar proportion (42±4%, 47±9% and 43±14% for RWE 1, RWE 2 and RWE 3, respectively). The scavenging activity of superoxide anion and 2,2-diphenyl-1-picrylhydrazyl radical was about the same with the three RWE. In hearts without RWE treatment, LVDP and +dP/dtmax were 61±4% and 62±5%, respectively, at the end of the reperfusion period. Infusion of RWE 1 and RWE 2 significantly improved postischemic recovery (LVDP and +dP/dtmax were 102±4% and 101±4% for RWE 1 and 92±5% and 91±5% for RWE 2, respectively) and attenuated the increase of LVEDP. RWE 3 did not improve either systolic or diastolic dysfunction. Conclusion: These data show that although the three nonalcoholic RWE exhibit a similar total antioxidant capacity, only two of them protect the heart against myocardial stunning, suggesting that the protective effect is not primarily linked to the antioxidant properties of the extracts.